2022
DOI: 10.1111/1475-6773.14044
|View full text |Cite
|
Sign up to set email alerts
|

Association between state Medicaid expansion status and health outcomes during the COVID‐19 pandemic

Abstract: Objective To assess post‐COVID‐19 changes in insurance coverage, health behaviors, and self‐assessed health among low‐income, non‐elderly adults by state Medicaid expansion status. Data Sources We used nationally representative survey data from the 2016 through 2020 Behavioral Risk Factor Surveillance System (BRFSS). The sample was restricted to adults aged 19–64 with household income below 138 percent of the federal poverty level ( N = 179,13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A recent report by Rakus et al described the importance of Medicaid in covering various low-income populations that may have contributed to lowering the impact of the pandemic. (26) However, further analysis should be encouraged to understand the impact on children, as seen in our study. Another significant socioeconomic disparity that we found consisted of the higher odds of mechanical ventilation among those who are from the lower quartile of median household income compared to those from the top quartile.…”
Section: Discussionmentioning
confidence: 92%
“…A recent report by Rakus et al described the importance of Medicaid in covering various low-income populations that may have contributed to lowering the impact of the pandemic. (26) However, further analysis should be encouraged to understand the impact on children, as seen in our study. Another significant socioeconomic disparity that we found consisted of the higher odds of mechanical ventilation among those who are from the lower quartile of median household income compared to those from the top quartile.…”
Section: Discussionmentioning
confidence: 92%
“…25,42 Another study reported no statistically significant difference in changes in days not in good mental health in the past 30 days during 2020 between expansion and non-expansion states overall, although the study found a statistically significant decline in this outcome for non-Hispanic Black individuals. 47 That study, however, included individuals up to 138% of the FPL and did not examine the effect separately for individuals below 100% of the FPL. In non-expansion states, individuals within 100-138% of the FPL are eligible for insurance marketplace subsidies, so including them in the sample may attenuate the effect of the Medicaid expansion.…”
Section: Introductionmentioning
confidence: 99%